Pengaruh Pengungkapan Sustainability Report terhadap Kinerja Keuangan pada Perusahaan Sub Sektor Tembakau yang Terdaftar di BEI - Anggella Rizki Veromikha; Rudy Kurniawan; Gita Desyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the relationship between the impact of sustainability report disclosure on the financial performance of companies in the tobacco subsector listed on the Indonesia Stock Exchange (IDX), as measured by Return on Assets (ROA) for the years 2020-2024. This study uses semi-annual data, with the first semester using data as of June 30 and the second semester using data as of December 31. This study yielded 40 observations with data spanning 10 time periods and 4 companies.The data was analyzed using the Random Effect Model (REM). The independent variable was measured using the Sustainability Disclosure Index (SRDI) based on GRI Standards, while financial performance is represented by Return on Assets (ROA), which is calculated as net income divided by total assets, derived from the companies financial statements. The findings indicate that disclosure related to economic aspects (X1) has a significant negative effect on financial performance, while disclosure related to environmental (X2) and social (X3) aspects does not have a significant impact on financial performance (ROA). However,simultaneously, disclosure from economic, environmental, and social aspects has a significant effect on financial performance.